RETRACTED: The Role of ’Ethical Brand’ and Its Effects on Company Reputation - Hoq, Mohammad Ziaul; Ali, Sulaiman M.; Alwi, Sharifah Faridah Syed (Administration and Management Review, 2011)
RETRACTION 16th July 2014: The first author of this paper, Mr Muhammad Ziaul Hoq, published it without the consent of the other authors (Dr Sulaiman Ali and Dr Sharifah Faridah Syed Alwi). Mr Hoq has now retracted the paper which was not his own research. The original research was conducted by Dr Sulaiman Ali for his PhD thesis and he was supervised by Dr Sharifah Faridah Syed Alwi. This paper reports the initial finding on examination of the effect of product and service quality on ‘ethical brand’, which in turn may influence a company’s reputation among industrial buyers that use electronic office equipment. The current study is informed by 50 experienced industrial buyers when buying electronic office equipment in Malaysia. The initial result does show that ethical brand has a full mediation impact on corporate reputation. In general, this study adds to the existing literature on branding and reputation by introducing the concept of the ‘ethical brand’ in order to understand the formation of a company reputation. Keyword: Ethical Brand; Company’s or Corporate Reputation; Industrial buyers Administration and Management Review Volume 22, No. 1, January, 2010 Page: 60-73 Uploaded Date: 2 December, 2011